2016
DOI: 10.1155/2016/2793516
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Biomechanics Determination in Healthy Myopic Subjects

Abstract: Purpose. To determine the corneal biomechanical properties by using the Ocular Response Analyzer™ and to investigate potential factors associated with the corneal biomechanics in healthy myopic subjects. Methods. 135 eyes from 135 healthy myopic subjects were included in this cross-sectional observational study. Cornea hysteresis (CH), corneal resistance factor (CRF), cornea-compensated intraocular pressure (IOPcc), and Goldmann-correlated intraocular pressure (IOPg) were determined with the Reichert Ocular Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
3
15
1
Order By: Relevance
“…We assumed that elongated myopic eyes have less rigidity to absorb external stress compared to emmetropic eyes, and thus, the globe tends to recoil backward faster. Our hypothesis is supported by previous ORA studies that showed lower corneal hysteresis in high myopia and suggested that myopic eyes had more flexibility and relative flaccidity [36][37][38][39]. Together with our data, the results suggest that the cornea in high myopia is less stiff than that in nonmyopia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We assumed that elongated myopic eyes have less rigidity to absorb external stress compared to emmetropic eyes, and thus, the globe tends to recoil backward faster. Our hypothesis is supported by previous ORA studies that showed lower corneal hysteresis in high myopia and suggested that myopic eyes had more flexibility and relative flaccidity [36][37][38][39]. Together with our data, the results suggest that the cornea in high myopia is less stiff than that in nonmyopia.…”
Section: Discussionsupporting
confidence: 91%
“…CH is a measurement of the energy absorption during the stress-strain cycle of viscoelastic composition which may represent the contribution of corneal resistance [34]. Studies from Shen et al and Qiu et al demonstrated that CH was significantly lower in high myopic eyes [35,36]. e Corvis ST enables real-time visualization of the corneal responses to applied external forces.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study shows that CRF was significantly lower in highly myopic eyes compared with emmetropic eyes,40 although there is another study that suggested no relationship between AL and CRF 41. In the current study, CRF increased with the decrease of PRAA.…”
Section: Discussioncontrasting
confidence: 51%
“…For hyperopic and for female patients, higher values for CRF have been observed. For highly myopic patients, other studies have registered lower values of the CH and CRF and higher values of IOPcc (Corneal Compensated Intraocular Pressure) and of IOPg (Goldmann Correlated IOP value) compared to the emmetropic, hyperopic patients or patients with medium or low myopia [ 31 - 34 ].…”
Section: Discussionmentioning
confidence: 99%